The Impact of the EU Deforestation-free Regulation on Indonesia's National Policies for Sustainable Coffee Commodity Management - Lipul Lipul; Nita Noriko (Universitas Al Azhar Indonesia, 2025)
As one of the world's largest coffee producers, Indonesia faces a new challenge with the enactment of the EU Deforestation-free Regulation (EUDR) by the European Union, a vital export market. This regulation requires that coffee products entering the EU market must be proven not to originate from land deforested after December 31, 2020. The objective of this article is to conduct an in- depth analysis of the EUDR's impact on the Indonesian coffee supply chain, evaluate the readiness of existing national policies, and identify policy responses that have been and need to be implemented. This study employs a qualitative method using a policy analysis approach and a comprehensive literature review of regulatory documents, government reports, and scientific publications. The results indicate significant challenges, particularly for millions of smallholder farmers, which include the obligation to provide geolocation data, fulfill due diligence requirements, and prove land legality, which is often undocumented. A gap was found between Indonesia's existing sustainable coffee management policies and the stringent requirements of the EUDR, especially concerning farm-level traceability. Although the Indonesian government has initiated several responsive measures, such as establishing a task force and diplomatic efforts, an acceleration in the development of an integrated and inclusive national traceability system is necessary. This article concludes that the EUDR, while a potential trade barrier, can also function as a catalyst to accelerate governance reforms in Indonesia's coffee sector towards more verifiable sustainability. Strategic policy implications are emphasized on strengthening farmer capacity, harmonizing regulations, and utilizing digital technology to ensure Indonesian coffee remains competitive in the global market.